Daily intake of watercress causes inhibition of experimental Ehrlich tumor growth - Débora Aparecida de Souza; Poliane M. Costa; Rosy Iara M. A. Ribeiro; Paula V. T. Vidigal; Flávia C. H. Pinto
ABSTRACT Introduction: Increasing cruciferous vegetable intake has been associated with reduced risk of cancer. Experimental and epidemiological studies suggest that the watercress it is a cruciferous vegetable with high concentration of compounds with recognized antitumor activity. Objective: To investigate the effects of daily intake of an aqueous solution of watercress on the growth of the experimental Ehrlich tumor (EET). Methods: Swiss mice were divided into three groups A, B and C (n = 6). The animals from the control group (A) received, by gavage, 0.05 ml of saline throughout the experiment. The animals in group B, from the first day of the experiment, received daily, by gavage, 0.05 ml of watercress aqueous solution (0.5 g/ml). The animals from group C began, on day 21, daily intake of this solution. At day 21.2 × 106 EET cells were inoculated subcutaneously in the left footpad of all mice, and tumor growth was assessed by measuring the thickness of the paw. On day 42, the animals were sacrificed and their footpads removed for histopathological analysis. Results: The animals from groups B and C have showed a suppression of tumor growth and a small area of necrosis compared to the animals of group A. Conclusion: The present study demonstrated that the daily intake of aqueous solution of watercress was able to activate a suppression of the EET growth, probably due to the main compounds with antitumor properties present in this vegetable.